Method for preparing 5-hydroxymethylfurfural by using composite film to photocatalyze glucose
The composite membrane photocatalyst assembled from a high-entropy sulfide film and a microporous zeolite molecular sieve film solves the problems of low conversion rate and poor selectivity in the preparation of HMF from glucose, achieving efficient and stable catalytic effects, and is suitable for the preparation of bio-based platform compounds.
Patent Information
- Application Number
- CN202511133093.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-12-19
AI Technical Summary
Existing technologies for the preparation of 5-hydroxymethylfurfural (HMF) from glucose have low conversion rates, poor selectivity, and poor catalyst stability, making it difficult to achieve large-scale and continuous production.
A composite membrane photocatalyst, which is a combination of a mesoporous high-carbon membrane photocatalyst and a mesoporous zeolite molecular sieve membrane, was used as the catalyst. The composite membrane assembled from a high-entropy sulfide membrane and a microporous zeolite molecular sieve membrane was used to achieve a highly efficient photocatalytic reaction and realize the conversion of glucose.
It improves the conversion rate of glucose and the selectivity of HMF. The catalyst has strong water resistance and good stability, avoiding equipment corrosion and environmental pollution caused by traditional catalysts, and realizing continuous production.
Smart Images

Figure CN121159484A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of bio-based platform compound preparation, and in particular to a method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose through a composite film. BACKGROUND
[0002] 5-hydroxymethylfurfural (HMF) is a bio-based platform compound, with a furan ring connected to a hydroxymethyl group at the 2 position and an aldehyde group at the 5 position, and has strong chemical activity, capable of undergoing various types of chemical reactions such as oxidation, hydrogenation, esterification, halogenation, polymerization, and hydrolysis. Using HMF as an intermediate, hundreds of compounds such as 2,5-furandicarboxylic acid (FDCA) and 2,5-furandicarboxaldehyde (DFF) can be prepared, and these compounds can be further extended downstream to develop a wide range of high-value-added products such as functional polyesters, adhesives, surfactants, pharmaceutical intermediates, and optoelectronic materials.
[0003] From the perspective of raw materials, there are currently two main routes for the large-scale production of HMF: the fructose route and the glucose route. Fructose has a similar furan ring configuration to HMF, and is more prone to ring contraction during dehydration. In addition, the hydroxyl group at the C2 position of the molecule is more likely to participate in intramolecular dehydration, resulting in higher reaction efficiency. However, the cost of fructose is relatively high, with a market price of over 8000 yuan per ton for many years, leading to a high market price of HMF, making it difficult to compete with similar petroleum-based chemicals. Industrial-grade glucose with a purity of 98% is generally only about one-third the price of fructose, and is more abundant and widely available. Using glucose as a raw material for the production of HMF can significantly reduce costs, and with mature production technology, it is expected to reduce the cost of HMF to less than 15000 yuan per ton.
[0004] The difficulties faced by the glucose route are low reaction conversion rate, poor selectivity, poor stability of the catalyst, and low maturity. Glucose needs to be isomerized to fructose by a Lewis acid catalyst, and then dehydrated by a Brønsted acid catalyst. This additional step increases reaction time and energy consumption, and may result in a decrease in overall yield due to insufficient isomerization efficiency. In addition, HMF is prone to rehydration in the presence of water to form byproducts such as levulinic acid (LA) and formic acid (FA), and may further undergo side reactions to form polymers or humins at high temperatures.
[0005] Patent CN 117736166 A discloses a method for preparing HMF from glucose using a composite hydrated chloride catalyst, which is a mixture of AlCl3.6H2O and SnCl4.5H2O. The composite hydrated chloride acts as a high-concentration solvent under high-temperature conditions, has the advantages of mild reaction conditions, simple operation, and low cost, but the metal chloride has certain corrosiveness to the equipment, and the composite hydrated metal chloride has a large viscosity at low temperature, which may block the pipeline. Patent CN 119488949 A discloses a catalyst for preparing HMF from glucose and a preparation method thereof. The catalyst is prepared from hydrochloric acid, metal chloride and nitrogen-containing organic matter, and the highest yield reaches 65%. However, the catalyst has problems of water resistance and recycling. Patent CN 113861139 A mixes a salt solution, a sugar compound and a catalyst and reacts to obtain a HMF yield of 99%. However, the catalyst is difficult to recover, and batch reaction is difficult to realize large-scale production. Based on this, the present application provides a method for preparing 5-hydroxymethylfurfural from glucose by composite membrane photocatalysis, which converts the process route of preparing HMF from glucose to have high conversion rate, fewer by-products, more water-resistant catalyst and better stability, and can realize continuous production. SUMMARY
[0006] The technical problem to be solved by the present application is to overcome the above problems and deficiencies, and to provide a method for preparing 5-hydroxymethylfurfural from glucose by composite membrane photocatalysis.
[0007] The root cause of low conversion rate of glucose to HMF is that the isomerization of glucose to fructose has a high energy barrier, which is the rate-determining step of the whole reaction. The reason for low selectivity is that HMF further hydrates to form other by-products. The present application designs a composite membrane with dual functions of reaction and separation. First, a high-entropy sulfide film with light absorption ability is introduced. The high-entropy sulfide has excellent photoelectric conversion ability, which can excite the configuration transformation of glucose molecules through photocatalysis, thereby improving the conversion rate of glucose. The structural stability brought by high-entropy effect makes it maintain active sites without loss in acidic reaction conditions. Then, a zeolite molecular sieve membrane rich in Brønsted acid sites and Lewis acid sites is introduced. The zeolite molecular sieve membrane catalyzes the dehydration reaction to synthesize HMF efficiently, and selectively permeates water molecules in one direction by using the size sieving effect of microporous zeolite molecular sieve, so as to realize in-situ separation of water molecules and HMF, thereby inhibiting the hydration side reaction of HMF with water molecules. The combination of mesoporous high-entropy sulfide film and microporous zeolite molecular sieve membrane is more conducive to the diffusion of glucose molecules and the desorption process of HMF molecules.
[0008] In order to achieve the above purpose, the technical scheme of the present application is as follows: The method for preparing 5-hydroxymethylfurfural by photocatalyzing glucose by the composite film of the application, using the composite film as a catalyst, mixing glucose aqueous solution and solvent under light conditions to carry out catalytic reaction, and obtaining crude 5-hydroxymethylfurfural production solution; the composite film is a composite film assembled by a mesoporous high-entropy sulfide film and a microporous zeolite membrane; the mesoporous high-entropy sulfide film is in-situ loaded on the surface of the microporous zeolite membrane by spraying and calcining; the composition of the mesoporous high-entropy sulfide includes Bi2S3, CoS, Fe2S3, Cr2S3 and CuS, wherein the molar ratio of elements Bi, Co, Fe, Cr and Cu is 2:1:1:1:1.
[0009] The specific operation method is as follows: glucose aqueous solution and solvent are continuously pumped into a mixer for mixing, pass through a preheater through the retentate side of the composite film, a cooler is arranged on the permeate side of the composite film for collecting water, CO2 gas is introduced, and continuous catalytic reaction is carried out under light conditions, and the end product is crude 5-hydroxymethylfurfural production solution.
[0010] The composite film provides photocatalytic and acid catalytic active sites, and selectively allows water molecules to permeate, and has the dual functions of reaction and separation.
[0011] Further, the average pore size of the mesoporous high-entropy sulfide film is 2.5-30 nm, and the thickness is 5-15 μm; the silicon-aluminum ratio of the zeolite membrane is 0.5-40, and the average pore size is 0.36-0.72 nm.
[0012] The preparation method of the composite film includes the following steps: five kinds of metal salt precursors are dissolved in ethanol, stirred uniformly, thiourea and ammonium acetate are added, high-pressure closed reaction is carried out at 80-120℃ for 6-8 hours, N,N-dimethyl dodecylamine is added after the reaction is completed, stirred uniformly, and aged for 10-12 hours to obtain a precursor solution, the precursor solution is uniformly sprayed on the surface of the zeolite membrane in the form of spraying, calcined at 400-600℃ under the protection of inert gas for 3-5 hours, and the composite film is obtained.
[0013] Further, the metal salt precursor is a metal nitrate, chloride, acetate or phosphate, and the addition amount of the metal salt precursor is calculated according to the molar ratio of Bi, Co, Fe, Cr and Cu metal elements 2:1:1:1:1.
[0014] Further, the addition amount of the thiourea is 0.9-2 times of the total metal molar amount, the addition amount of the ammonium acetate is 1.1-2.1 times of the total metal molar amount, and the addition amount of the N,N-dimethyl dodecylamine is 1.5-3.5 times of the total metal molar amount.
[0015] Further, the wavelength range of light under the light condition is 280-400 nm, and the light intensity is 300-600 mWcm-2.-2 .
[0016] Further, the mass fraction of glucose in the aqueous glucose solution is 80-90%.
[0017] Further, the solvent is at least one of tetrahydrofuran, methyl isobutyl ketone, acetone, dimethyl carbonate, isopropyl alcohol or gamma-valerolactone; and the mass flow ratio of the organic solvent and the aqueous glucose solution is 1.5-2:1.
[0018] The schematic diagram of the method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose on the composite film in the application is shown in Figure 6 The glucose molecules are photocatalyzed on the surface of the high-entropy sulfide film to realize isomerization conversion of glucose to fructose; the fructose molecules are dehydrated and converted into 5-hydroxymethylfurfural under the catalysis of acid sites of the zeolite molecular sieve membrane; and the water molecules and solvent water molecules are condensed and collected through the zeolite molecular sieve membrane under the action of osmotic pressure difference.
[0019] The beneficial effects of the application are as follows: 1. The high-entropy sulfide film has excellent photoelectric conversion capacity, and the glucose molecules are excited to undergo configuration conversion by photocatalysis, thereby improving the conversion rate of glucose; in addition, the structural stability brought by the high-entropy effect enables the active sites to remain active in acidic reaction conditions.
[0020] 2. The zeolite molecular sieve membrane is rich in Brønsted acid sites and Lewis acid sites, and can efficiently catalyze the dehydration reaction to synthesize HMF; at the same time, the size sieving effect of the microporous zeolite molecular sieve membrane is used to selectively permeate water molecules in one direction, so as to realize in-situ separation of water molecules and HMF, inhibit the hydration side reaction of HMF and water, and improve the reaction selectivity.
[0021] 3. The catalyst has strong water resistance, good stability, is clean and environmentally friendly, avoids equipment corrosion and environmental problems caused by traditional inorganic acid catalysts and metal chloride catalysts, and has relatively mild reaction conditions. BRIEF DESCRIPTION OF DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or prior art description. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor.
[0023] Figure 1 The SEM electron microscope image of the surface of the high-entropy sulfide film prepared in Embodiment 1 of the application.
[0024] Figure 2The energy spectrum of the high-entropy sulfide film prepared in Example 1 of the present application.
[0025] Figure 3 The high-performance liquid chromatogram of the product solution prepared in Example 1 of the present application.
[0026] Figure 4 The HMF prepared in Example 1 of the present application 1 H nuclear magnetic spectrum.
[0027] Figure 5 The HMF prepared in Example 1 of the present application 13 C nuclear magnetic spectrum.
[0028] Figure 6 A schematic diagram of a method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose using a composite membrane according to the present application.
[0029] Figure 7 A schematic diagram of a device for preparing 5-hydroxymethylfurfural by photocatalysis of glucose using a composite membrane according to the present application, wherein 1 is a mixer, 2 is a preheater, 3 is a front back pressure valve, 4 is a composite membrane permeation measurement, 5 is a light source and heater, 6 is a composite membrane, 7 is a composite membrane, 8 is a condenser, 9 is a rear back pressure valve, and 10 is a vacuum pump. DETAILED DESCRIPTION
[0030] In the following description, numerous specific details are set forth in order to provide a thorough understanding of the present application. However, it will be apparent to one skilled in the art that the present application can be practiced without one or more of these specific details. In other instances, well-known features have not been described in detail to avoid obscuring aspects of the present application.
[0031] For a thorough understanding of the present application, a detailed description will be made in the following description with reference to the drawings, to illustrate a method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose using a composite membrane according to the present application. It is apparent that the implementation of the present application is not limited to the specific details described in the field of 5-hydroxymethylfurfural synthesis familiar to those skilled in the art. The preferred embodiments of the present application are described in detail as follows, however, in addition to these detailed descriptions, the present application can have other implementations.
[0032] In the following embodiments, the component analysis of the product uses a high-performance chromatograph, Waters Arc HPLC, with the following detection conditions: C18 column, mobile phase of 6:4 methanol-water solution, ultraviolet light detector, detection wavelength of 284 nm, and column temperature of 40°C. The yield and selectivity of the reaction are calculated according to the liquid chromatography analysis results by the external standard method. The SEM and EDS characterization of the high-entropy sulfide film is determined by a field emission scanning electron microscope, JEOL JSM-7900F. The nuclear magnetic spectrum of HMF is determined by a Bruker nuclear magnetic resonance spectrometer, AVANCE NEO 600. The glucose, organic solvents such as tetrahydrofuran, zeolite molecular sieve membrane ethanol, metal nitrate, and the like used in the present application are all commercially available. The water used is laboratory-made.
[0033] Example 1 The preparation steps of the composite film in this example are as follows: 97.0 g of Bi(NO3)3·5H2O, 29.1 g of Co(NO3)2·6H2O, 40.4 g of Fe(NO3)2·9H2O, 40.0 g of Cr(NO3)3·9H2O, and 24.1 g of Cu(NO3)2·3H2O were weighed out, dissolved in 1200 mL of anhydrous ethanol, stirred for 30 minutes, 68.4 g of thiourea and 50.8 g of ammonium acetate were added, stirred for 30 minutes, and reacted in a pressure-resistant reaction kettle at 120°C for 8 hours. After the reaction was completed, 191.7 g of N,N-dimethyldodecylamine was added, stirred for 30 minutes and dispersed uniformly for 30 minutes by ultrasonic, and then aged at room temperature for 12 hours. A precursor solution was obtained. The precursor solution was uniformly sprayed in the form of a mist onto the surface of the beta zeolite molecular sieve membrane, and calcined at 400°C for 5 hours under the protection of nitrogen to obtain a composite film, wherein the thickness of the high-entropy sulfide film was 10 μm.
[0034] The method for photocatalyzing glucose to prepare 5-hydroxymethylfurfural by the composite film in this example is as follows: As shown in Figure 7 , glucose was dissolved in water to prepare a glucose aqueous solution with a mass fraction of 80%, and the glucose aqueous solution and methyl isobutyl ketone solvent were respectively introduced into a mixer 1 at a flow rate of 15 mL / min and 10 mL / min, preheated to 80°C by a preheater 2, and passed through the surface of the composite membrane in a continuous flow mode. The composite membrane was provided with a cooler 8 and connected to a vacuum pump 10, and the vacuum degree was set to -95 KPa. The residence time was 40 minutes, the reaction temperature was 80°C, the pressure was maintained at 0.5 MPa by adjusting the front back pressure valve 3 and the rear back pressure valve 9, and the light intensity of the ultraviolet lamp (280 nm wavelength) was 300 mW·cm -2 Under the irradiation of the ultraviolet lamp (280 nm wavelength), the reaction temperature was controlled to be 80°C, the pressure was maintained at 0.5 MPa by adjusting the front back pressure valve 3 and the rear back pressure valve 9, the residence time was 40 minutes, and the light intensity of the ultraviolet lamp (280 nm wavelength) was 300 mW·cm-2. The crude 5-hydroxymethylfurfural product solution was obtained, the solvent was removed to obtain 5-hydroxymethylfurfural, and the conversion rate of glucose was 90.1% and the selectivity of HMF was 85.6% by high-performance liquid chromatography analysis.
[0035] In this embodiment, the SEM image of the high-entropy sulfide film surface is attached. Figure 1 As shown, the surface of the composite membrane has a loose network morphology, exhibiting obvious porous structure characteristics.
[0036] The energy spectrum of high-entropy sulfide thin films is attached. Figure 2 As shown, the main elements present on the surface of the composite membrane are Bi, Co, Fe, Cr, Cu, and S.
[0037] The high-performance liquid chromatogram of the crude 5-hydroxymethylfurfural product is shown below. Figure 3 As shown, the characteristic peak of HMF is at 5.987 minutes, with a peak area ratio of 99.2%.
[0038] The purified HMF obtained 1 H spectrum as shown Figure 4 As shown. 1 H NMR (600 MHz, Chloroform-d) δ=9.49 (s, 1H), 7.16 (d, J = 3.5 Hz, 1H), 6.45 (d, J = 3.5 Hz, 1H), 4.64 (s, 2H), 3.09 (s, 1H). The purified HMF obtained 13 C spectrum as shown Figure 5 As shown. 13 C NMR (151 MHz, Chloroform-d) δ=176.79,159.91, 151.25, 122.23, 109.02, 56.44. Example 2 The preparation steps of the composite membrane in this embodiment are as follows: Weigh 48.5g Bi(NO3)3·5H2O, 14.55gCo(NO3)2·6H2O, 20.2gFe(NO3)2·9H2O Five metal salts, namely 20g Cr(NO3)3·9H2O and 12.05g Cu(NO3)2·3H2O, were dissolved in 600mL anhydrous ethanol and stirred for 30 minutes. Then, 45.6g thiourea and 48.51g ammonium acetate were added and stirred for another 30 minutes. The mixture was then sealed in a pressure-resistant reactor at 100℃ for 7 hours. After the reaction was completed, 127.8g N,N-dimethyldodecylamine was added, and the mixture was stirred for 30 minutes and then sonicated for 30 minutes to disperse the mixture evenly. The mixture was then allowed to stand at room temperature for 10 hours to obtain a precursor solution. The precursor solution was then sprayed evenly onto the surface of a ZSM-5 zeolite molecular sieve membrane. The membrane was then calcined at 500℃ for 3.5 hours under nitrogen protection to obtain a composite membrane, in which the thickness of the high-entropy sulfide film was 5μm.
[0039] The method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose in the composite membrane of the embodiment is as follows: The glucose was dissolved in water to prepare a glucose aqueous solution with a mass fraction of 90%, and the glucose aqueous solution and tetrahydrofuran solvent were respectively introduced into a mixer at a flow rate of 20 mL / min and 10 mL / min, preheated to 85℃, and passed through the surface of the composite membrane in a continuous flow mode. The other side of the composite membrane was vacuumized, and the vacuum degree was set to -95 KPa. The reaction was carried out at a power density of 600 mW·cm -2 Under the irradiation of an ultraviolet lamp (400 nm wavelength), the reaction temperature was controlled to be 100℃, the pressure was 1.3 MPa, and the residence time was 30 minutes. The crude 5-hydroxymethylfurfural solution was obtained, and 5-hydroxymethylfurfural was obtained by removing the solvent. High performance liquid chromatography analysis showed that the conversion rate of glucose was 96.3%, and the selectivity of HMF was 87.3%.
[0040] Example 3 The preparation steps of the composite membrane of the embodiment are as follows: 79 g of Bi(NO3)3, 18.3 g of Co(NO3)2, 18 g of Fe(NO3)2, 23.8 g of Cr(NO3)3, and 18.7 g of Cu(NO3)2 were weighed, dissolved in 960 mL of anhydrous ethanol, stirred for 30 minutes, 41.0 g of thiourea and 69.3 g of ammonium acetate were added, stirred for 30 minutes, and then placed in a pressure-resistant reaction kettle for closed reaction at 80℃ for 6 hours. After the reaction was completed, 447.3 g of N,N-dimethyl dodecylamine was added, stirred for 30 minutes, and dispersed uniformly for 30 minutes by ultrasonic, and then left to stand at room temperature for aging for 12 hours. The precursor solution was uniformly sprayed on the surface of the mordenite molecular sieve membrane in the form of spraying, and then calcined at 450℃ for 3 hours under the protection of nitrogen to obtain the composite membrane. The thickness of the high-entropy sulfide film was 15 μm.
[0041] The method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose in the composite membrane of the embodiment is as follows: The glucose was dissolved in water to prepare a glucose aqueous solution with a mass fraction of 85%, and the glucose aqueous solution and acetone solvent were respectively introduced into a mixer at a flow rate of 17.5 mL / min and 10 mL / min, preheated to 85℃, and passed through the surface of the composite membrane in a continuous flow mode. The other side of the composite membrane was vacuumized, and the vacuum degree was set to -95 KPa. The reaction was carried out at a power density of 500 mW·cm -2 Under the irradiation of an ultraviolet lamp (380 nm wavelength), the reaction temperature was controlled to be 95℃, the pressure was 1.0 MPa, and the residence time was 35 minutes. The crude 5-hydroxymethylfurfural solution was obtained, and 5-hydroxymethylfurfural was obtained by removing the solvent. High performance liquid chromatography analysis showed that the conversion rate of glucose was 85.1%, and the selectivity of HMF was 73.1%.
[0042] Example 4 The preparation steps of the composite film of the present example are as follows: Take 39.5g Bi(NO3)3, 9.15g Co(NO3)2, 9g Fe(NO3)2, 11.9g Cr(NO3)3 and 9.35g Cu(NO3)2 five kinds of metal salt, dissolve in 800mL anhydrous ethanol, stir for 30 minutes, add 41.04g thiourea and 46.2g ammonium acetate, stir for 30 minutes, seal reaction in pressure reactor at 110℃ for 6.5 hours, after the end, add 191.7g N,N-dimethyl dodecylamine, stir for 30 minutes and ultrasonic for 30 minutes to disperse uniformly, room temperature standing for 110.5 hours, get the precursor solution, spray the precursor solution uniformly on the surface of Y type zeolite molecular sieve membrane in the form of spray, under the protection of nitrogen, high temperature calcination at 600℃ for 4 hours, get the composite film, the thickness of high entropy sulfide film is 12μm.
[0043] The method for preparing 5-hydroxymethylfurfural by photocatalytic glucose of the composite film of the present example, the steps are as follows: Dissolve glucose in water to prepare a 90% mass fraction glucose aqueous solution, mix with dimethyl carbonate solvent, respectively at 15.5mL / min and 9mL / min into the mixer, preheat to 80℃, pass through the surface of the composite film in a continuous flow mode, vacuumize the other side of the composite film, the vacuum degree is set to-90KPa, under the irradiation of ultraviolet lamp (300nm wavelength), control the reaction temperature to be 120℃, the pressure is 0.5 MPa, the residence time is 40 minutes, the end gets the crude 5-hydroxymethylfurfural solution, remove the solvent to get 5-hydroxymethylfurfural, through high performance liquid chromatography analysis, the conversion rate of glucose is 80.7%, the selectivity of HMF is 87.6%. -2 Under the irradiation of ultraviolet lamp (300nm wavelength), control the reaction temperature to be 120℃, the pressure is 0.5 MPa, the residence time is 40 minutes, the end gets the crude 5-hydroxymethylfurfural solution, remove the solvent to get 5-hydroxymethylfurfural, through high performance liquid chromatography analysis, the conversion rate of glucose is 80.7%, the selectivity of HMF is 87.6%.
[0044] Example 5 The preparation steps of the composite film of the present example are as follows: Take 9.5g BiCl3, 18.43g Co3(PO4)2, 1.9g FeCl2, 2.4g CrCl3 and 2.0g CuCl2 five kinds of metal salt, dissolve in 300mL anhydrous ethanol, stir for 30 minutes, add 9.51g thiourea and 11.62g ammonium acetate, stir for 30 minutes, seal reaction in pressure reactor at 115℃ for 7.5 hours, after the end, add 66.64g N,N-dimethyl dodecylamine, stir for 30 minutes and ultrasonic for 30 minutes to disperse uniformly, room temperature standing for 11 hours, get the precursor solution, spray the precursor solution uniformly on the surface of Y type zeolite molecular sieve membrane in the form of spray, under the protection of nitrogen, high temperature calcination at 550℃ for 4.55 hours, get the composite film, the thickness of high entropy sulfide film is 8μm.
[0045] The method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose in the composite membrane of the embodiment is as follows: Glucose was dissolved in water to prepare a glucose aqueous solution with a mass fraction of 80%, which was mixed with isopropyl alcohol solvent at 15 mL / min and 10 mL / min respectively into a mixer, preheated to 80℃, and passed through the surface of the composite membrane in a continuous flow mode. The other side of the composite membrane was vacuumed, the vacuum degree was set to-95 KPa, and the composite membrane was irradiated with an ultraviolet lamp (400 nm wavelength) at a power of 500 mW·cm -2 Under the irradiation of the ultraviolet lamp (400 nm wavelength), the reaction temperature was controlled to be 90℃, the pressure was 1.2 MPa, the residence time was 40 minutes, and the crude 5-hydroxymethylfurfural solution was obtained. After removing the solvent, 5-hydroxymethylfurfural was obtained. Through high performance liquid chromatography analysis, the conversion rate of glucose was 84.5%, and the selectivity of HMF was 79.4%.
[0046] Embodiment 6 The preparation steps of the composite membrane of the embodiment are as follows: 48.5g Bi(NO3)3·5H2O, 29.1g Co(NO3)2·6H2O, 40.4g Fe(NO3)2·9H2O, 40.0g Cr(NO3)3·9H2O and 24.1g Cu(NO3)2·3H2O were weighed, dissolved in 600mL anhydrous ethanol, stirred for 30 minutes, 36.5g thiourea and 41.6g ammonium acetate were added, stirred for 30 minutes, and then placed in a pressure-resistant reaction kettle for 8 hours of closed reaction at 120℃. After the reaction was completed, 140.6g N,N-dimethyl dodecylamine was added, stirred for 30 minutes and ultrasonically dispersed for 30 minutes to make it uniformly dispersed. After being left to stand at room temperature for 12 hours, a precursor solution was obtained. The precursor solution was uniformly sprayed on the surface of the beta zeolite molecular sieve membrane in the form of spraying. Under the protection of nitrogen, the composite membrane was obtained by calcining at a high temperature of 580℃ for 5 hours, wherein the thickness of the high-entropy sulfide film was 13μm.
[0047] The method for preparing 5-hydroxymethylfurfural by photocatalysis of glucose in the composite membrane of the embodiment is as follows: Glucose was dissolved in water to prepare a glucose aqueous solution with a mass fraction of 80%, which was mixed with isopropyl alcohol solvent at 15 mL / min and 10 mL / min respectively into a mixer, preheated to 80℃, and passed through the surface of the composite membrane in a continuous flow mode. The other side of the composite membrane was vacuumed, the vacuum degree was set to-95 KPa, and the composite membrane was irradiated with an ultraviolet lamp (400 nm wavelength) at a power of 500 mW·cm -2 Under the irradiation of the ultraviolet lamp (400 nm wavelength), the reaction temperature was controlled to be 90℃, the pressure was 1.2 MPa, the residence time was 40 minutes, and the crude 5-hydroxymethylfurfural solution was obtained. After removing the solvent, 5-hydroxymethylfurfural was obtained. Through high performance liquid chromatography analysis, the conversion rate of glucose was 84.5%, and the selectivity of HMF was 79.4%.
[0048] Comparative Example 1 The difference between this comparative example and Example 1 is that the composite membrane is replaced by a beta zeolite molecular sieve membrane, and the reaction steps and conditions are the same as those of Example 1, to obtain a crude 5-hydroxymethylfurfural product solution. Through high performance liquid chromatography analysis, the conversion rate of glucose is 33.5%, and the selectivity of HMF is 56.9%.
[0049] Comparative Example 2 The difference between this comparative example and Example 2 is that the composite membrane is replaced by a ZSM-5 zeolite molecular sieve membrane, and the reaction steps and conditions are the same as those of Example 2, to obtain a crude 5-hydroxymethylfurfural product solution. Through high performance liquid chromatography analysis, the conversion rate of glucose is 35.6%, and the selectivity of HMF is 60.9%.
[0050] Comparative Example 3 The difference between this comparative example and Example 3 is that the composite membrane is replaced by a mordenite zeolite molecular sieve membrane, and the reaction steps and conditions are the same as those of Example 3, to obtain a crude 5-hydroxymethylfurfural product solution. Through high performance liquid chromatography analysis, the conversion rate of glucose is 18.7%, and the selectivity of HMF is 65.4%.
[0051] Comparative Example 4 The difference between this comparative example and Example 4 is that the composite membrane is replaced by a Y-type zeolite molecular sieve membrane, and the reaction steps and conditions are the same as those of Example 4, to obtain a crude 5-hydroxymethylfurfural product solution. Through high performance liquid chromatography analysis, the conversion rate of glucose is 26.8%, and the selectivity of HMF is 54.4%.
[0052] Comparative Example 5 The difference between this comparative example and Example 5 is that the composite membrane is replaced by a Y-type zeolite molecular sieve membrane, and the reaction steps and conditions are the same as those of Example 4, to obtain a crude 5-hydroxymethylfurfural product solution. Through high performance liquid chromatography analysis, the conversion rate of glucose is 25.9%, and the selectivity of HMF is 69.8%.
[0053] Comparative Example 6 The difference between this comparative example and Example 6 is that the composite membrane is replaced by a beta zeolite molecular sieve membrane, and the reaction steps and conditions are the same as those of Example 1, to obtain a crude 5-hydroxymethylfurfural product solution. Through high performance liquid chromatography analysis, the conversion rate of glucose is 27.1%, and the selectivity of HMF is 73.4%.
[0054] The results of the examples and comparative examples are shown in Table 1.
[0055] Table 1 According to the test data of examples 1-6 and comparative examples 1-6 shown in table 1, although the zeolite molecular sieve membrane is used in the comparative examples, the conversion rate is not more than 50% due to the weak catalytic activity of isomerization of glucose to fructose. In the examples, glucose is first isomerized to fructose under the photocatalysis of mesoporous high-entropy sulfide film, and then dehydrated to generate HMF, which significantly improves the reaction selectivity of HMF, and the HMF yield is >60%.
[0056] The above description is merely preferred embodiments of the present application, but not to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for photocatalytic glucose conversion to 5-hydroxymethylfurfural using a composite film, characterized in that: The composite membrane is used as a catalyst to catalyze the mixture of a glucose aqueous solution and a solvent under light to obtain a crude 5-hydroxymethylfurfural production solution; the composite membrane is a composite membrane assembled by a mesoporous high-entropy sulfide film and a microporous zeolite membrane, the mesoporous high-entropy sulfide film is in-situ loaded on the surface of the microporous zeolite membrane by a spraying-calcination method, and the mesoporous high-entropy sulfide composition comprises Bi2S3, CoS, Fe2S3, Cr2S3 and CuS, wherein the molar ratio of the elements Bi, Co, Fe, Cr and Cu is 2:1:1:1:
1.
2. The method according to claim 1, wherein the composite film is used for photocatalytic preparation of 5-hydroxymethylfurfural from glucose. The glucose aqueous solution and the solvent are continuously pumped into a mixer, mixed, passed through a preheater, and passed through the retentate side of the composite membrane, a cooler is arranged on the permeate side of the composite membrane for collecting water, CO2 gas is introduced, and continuous catalytic reaction is carried out under light, and the end product is a crude 5-hydroxymethylfurfural production solution.
3. The method of photocatalytic glucose to 5-hydroxymethylfurfural production by composite film according to claim 1, characterized in that: The average pore diameter of the mesoporous high-entropy sulfide film is 2.5-30 nm, and the thickness is 5-15 μm; the silicon-aluminum ratio of the microporous zeolite membrane is 0.5-40, and the average pore diameter is 0.36-0.72 nm.
4. The method of photocatalytic glucose to 5-hydroxymethylfurfural production by composite film according to claim 1, characterized in that: The preparation method of the composite membrane comprises the following steps: dissolving five kinds of metal salt precursors in ethanol, stirring uniformly, adding thiourea and ammonium acetate, carrying out high-pressure closed reaction at 80-120 DEG C for 6-8 hours, adding N,N-dimethyldodecylamine after the reaction is completed, stirring uniformly, standing for 10-12 hours, obtaining a precursor solution, spraying the precursor solution in the form of spray on the surface of the zeolite membrane, calcining at 400-600 DEG C under the protection of inert gas for 3-5 hours, and obtaining the composite membrane.
5. The method of photocatalytic glucose to 5-hydroxymethylfurfural production by composite film according to claim 4, characterized in that: The metal salt precursors are metal nitrate, chloride, acetate or phosphate, and the addition amount of the metal salt precursors is 2:1:1:1:1 according to the molar ratio of the Bi, Co, Fe, Cr and Cu metal elements.
6. The method of photocatalytic glucose to 5-hydroxymethylfurfural production by composite film according to claim 4, characterized in that: The addition amount of the thiourea is 0.9-2 times the total metal molar amount, the addition amount of the ammonium acetate is 1.1-2.1 times the total metal molar amount, and the addition amount of the N,N-dimethyldodecylamine is 1.5-3.5 times the total metal molar amount.
7. The method of photocatalytic glucose to 5-hydroxymethylfurfural production by composite film according to claim 1, characterized in that: The wavelength range of the light under the light condition is 280-400 nm, and the light intensity is 300-600 mWcm -2 .
8. The method of photocatalytic glucose to 5-hydroxymethylfurfural production by composite film according to claim 1, characterized in that: The mass fraction of glucose in the glucose aqueous solution is 80-90%.
9. The method of claim 1, wherein the composite film photocatalyzing glucose to 5-hydroxymethylfurfural is characterized by: The solvent is at least one of tetrahydrofuran, methyl isobutyl ketone, acetone, dimethyl carbonate, isopropyl alcohol or gamma-valerolactone; and the mass flow ratio of the organic solvent to the glucose aqueous solution is 1.5-2:
1.
10. The method of claim 1, wherein the composite film is prepared by a method comprising: (a) preparing a solution of a metal oxide and a polymer; (b) coating the solution on a substrate to form a film; (c) drying the film; (d) calcining the film; and (e) coating the film with a solution of a metal oxide and a polymer. The catalytic reaction temperature is 80-120 DEG C, and the reaction pressure is 0.5-1.3 MPa.
Citation Information
Patent Citations
Method for preparing 5-hydroxymethylfurfural
CN113861139A
Catalyst for preparing 5-hydroxymethylfurfural through sugar conversion as well as preparation method and application of catalyst
CN119488949A
Cited By
Mesoporous high-entropy sulfide catalyst, preparation method thereof and application of mesoporous high-entropy sulfide catalyst in preparation of formic acid by electrooxidation of PET hydrolysate
CN122059457A